Assessing Barriers to Cancer Screening and Early Detection in Older Adults in Saudi Arabia: A Mixed-Methods Approach to Oncology Nursing Practice Implications - Abdulaziz M. Alodhialah; Ashwaq A. Almutairi; Mohammed Almutairi (Current Oncology)
Background: Access to cancer screening services is crucial for early detection and improved survival rates, yet older adults in Saudi Arabia face significant barriers. Recent data from the Saudi Health Ministry indicate that cancer incidence in this demographic is rising, underscoring the urgent need for enhanced screening efforts. This study explores the factors influencing cancer screening behaviors among older adults in Riyadh, using a mixed-methods approach to identify and address these barriers effectively. Methods: The study integrated quantitative data from 100 participants aged 60 and above who attended King Saud University-affiliated healthcare centers, and qualitative insights from 20 semi-structured interviews. The Barriers to Cancer Screening Scale (BCSS) quantitatively assessed barriers, while the thematic analysis of interview data helped identify key themes. Results: Findings revealed significant barriers, categorized into three primary themes: accessibility challenges, psychological barriers, and social influences. These include logistical difficulties related to transportation and service availability, fears and anxieties regarding cancer diagnoses, and a lack of family support and cultural stigma, all of which impact participants’ willingness to engage in screening. Conclusion: The study underscores the multifaceted barriers faced by older adults in accessing cancer screening in Saudi Arabia. Tailored interventions that address logistical, psychological, and social factors are essential to enhance screening uptake and ensure equitable access to preventive services. These findings contribute to the ongoing discussions on public health strategies and underscore the necessity for community and healthcare provider engagement to improve cancer screening rates in this population.